The impact of fall-related loading rate on the formation of micro-damage in human cortical bone fracture - Dapaah, D.; Martel, D. R.; Laing, A. C.; Willett, T. L. (Journal of Biomechanics, 2022)
The quest for better predictive tools as well as new preventative and therapeutic measures for bone fragility and fracture has highlighted the need for greater mechanistic understanding of the bone fracture process. Cortical bone, the major load bearing part of the bone, employs different toughening mechanisms to either inhibit or slow down crack growth which leads to fracture. Among these toughening mechanisms, is the formation of a micro-damage process zone (MDPZ) around the region of the propagating crack. Investigations into the MDPZ to date have primarily been based on quasi-static or cyclic loading rate experiments which do not necessarily replicate physiological fracture rates. Consequently, the impact of fall-related loading rates on the formation of the micro-damage process zone was investigated comparing these to quasi-static loading rate equivalents. The size of MDPZ was found to be 42% smaller in the high-rate group compared to the quasi-static rate group. The smaller MDPZ size was associated with a brittle, unstable fracture behaviour and an overall smaller fracture resistance measure (). This result points to the possibility of a strain rate hardening mechanism at the heart of micro-damage formation, which is hampered under high loading rates, resulting in lower overall fracture resistance.